MEMANTAPKAN LANDASAN HUKUM FORMIL SEBAGAI ALAT SINGKRONISASI DAN HARMONISASI PERATURAN PERUNDANG - UNDANGAN - Insan Tajali Nur (Yuriska: Jurnal Ilmiah Hukum, 2018)
The regulation in the Regional Regulation is faced with the problem of how the Regional Regulation can regulate the affairs of authority in accordance with the characteristics of the region. But it does not conflict with the higher laws and regulations. One of the problems is Disharmony legislation resulting in differences in interpretation in its implementation; the emergence of legal uncertainty; Legislation is not carried out effectively and efficiently, and legal dysfunction, in a disharmonic manner, the rules and regulations - Invitation under the above laws and regulations is an evaluation material. But de facto, there are a number of draft regulations based on rules outside the order of the laws.Whereas in Article 7 paragraph 2 of Act Number 12 of 2011 confirms the strength of the laws of the legislation in accordance with the hierarchy in paragraph 1. Continued related to Article 140 paragraph (3) of Law Number 23 of 2014 concerning the Establishment of Legislation as has undergone the second amendment to the Law of the Republic of Indonesia Number 9 of 2015 concerning Regional Government, states that the procedure for preparing a draft Regional Regulation from the Governor or Regent / Mayor is regulated by a Presidential Regulation. Then Article 141 paragraph (2) of the Law on Regional Government states that further Provisions concerning the procedure for preparing the Regional Regulation are regulated in the DPRD Rules of Procedure.Based on the principle of the formation of laws and regulations, the Minister of Home Affairs's regulation violates the principle of conformity between types and materials of content, because the substance should be the material of the contents of the Presidential Regulation as part of the hierarchy of the Order of Regulations - Invitation and the contents of the DPRD Rules of Procedure.